Paragon or pariah? The consequences of being conspicuously rich in China's new economy - Firth, Michael; He, Xianjie; Rui, Oliver M.; Xiao, Tusheng (Journal of Corporate Finance, 2014)
In some cultures vast personal wealth is lauded whereas in others, it is viewed with suspicion and contempt. In recent years, a super rich elite of business people has emerged in China, and, given the country's cultural and socialist past, we believe that people are more likely to react negatively to reports of conspicuous wealth. To test our arguments, we examine the reactions to and consequences of China's entrepreneurs being included on the Hurun Rich List. We find negative consequences for stock market traded firms controlled by the Rich List entrepreneurs: stock prices decline, government subsidies are reduced, and the named entrepreneurs are more likely to be investigated. These effects are strongest in rent-seeking industries and are mitigated by philanthropy.